SWOT-ANALYSIS OF ORGANIZATION FOR INCLUDING A FOOTBALL GAME IN THE EDUCATIONAL PROGRAMME ON PHYSICAL CULTURE AND SPORT FOR FEMALE STUDENTS - G. Dyakova; T. Dyakov (Trakia Journal of Sciences)
SWOT-analysis has been conducted with 41 participants – lecturers from Tracian University – Stara Zagora, National Sports Academy “Vasil Levski”, Medical University – Sofia, Russe University “Angel Kanchev”, Sofia University “St. Kliment Ohridski”, University of National and World Economy- Sofia; football sportsmen from the representative team of Tracian University – Stara Zagora, trainers. The purpose of the analysis is to reveal the strong and weak points, possibilities and challenges of the organization with the inclusion of the football game in the educational programme, on Physical culture and sport, for female students. SWOT-analysis has been applied for settlement of the research purpose set. Results of SWOT-analysis give us a reason for deducing practicalapplication recommendations, and namely: to realize a close contact between the institutions, preparing experts on female football and the institutions that would make use of these experts; to update the methods of education on female football with newer and current means, methods and forms; to increase the activity of institutions, responsible for creation of suitable material base in the Higher schools for practicing of football by men and women; to enhance the motive activity and motivation of female students on football study; the available preconditions for practicing the female football in Tracian University should find its realization via the inclusion of this sport in the educational programme on Physical education and sport.